Radiocarbon and Helium Isotope Constraints on Deep Ocean Ventilation and Mantle‐3He Sources. Issue 5 (9th May 2019) - DeVries, Tim; Holzer, Mark
Abstract: Radiocarbon (Δ 14 C) and helium isotopes ( δ 3 He) have long been used to constrain the ocean's ventilation rates and to trace regional deep ocean circulation pathways, but they have not been fully exploited together to constrain the deep circulation in global models. Here we assimilate Δ 14 C and δ 3 He measurements into a global ocean circulation inverse model (OCIM) to jointly constrain the deep ocean circulation and the rate of mantle‐helium injection at seafloor spreading ridges. We find that the new version of the inverse model (OCIM2) matches the observed Δ 14 C and δ 3 He distributions much better than a previous version (OCIM1) that assimilated objectively mapped Δ 14 C but not δ 3 He. OCIM2 features faster‐ventilated bottom waters and slower‐ventilated intermediate‐depth waters in the Pacific and Indian Oceans. The mean time since last ventilation (ideal mean age) in Pacific bottom waters is up to 150 years younger, while middepth Pacific waters are up to several hundred years older. The δ 3 He constraints are shown to be important for estimates of the mean time to next ventilation in the Pacific Ocean. The δ 3 He constraints also favor jet‐like currents in the deep equatorial Pacific to capture realistic westward propagating helium plumes emanating from the East Pacific Rise. The globally integrated mantle‐helium source is 585–672 mol/year, compared to 400–1, 000 mol/year from previous estimates. The major regional difference occurs in the Southern Ocean, where the OCIM2 mantle‐helium source is up to threefold smaller than estimates based on ridge spreading rates. Key Points: Radiocarbon and helium isotope measurements provide complementary constraints on the deep ocean ventilation in a circulation inverse model The assimilated circulation produces realistic westward propagating 3 He plumes in the deep Eastern Tropical Pacific The jointly assimilated globally integrated mantle‐ 3 He source is 585–672 mol/year